An information congestion control scheme in the Internet of Vehicles: A bargaining game approach. (February 2017) - Chen, Chen; Hu, Jinna; Sui, Jisheng; Zhou, Yang
Abstract: In VANETs (Vehicular Ad Hoc Networks), the information exchange plays an important role for context awareness. However, at intersections, a channel congestion is likely occurring if no control scheme is applied for the exchange especially when the vehicle density is high. To solve this problem, a congestion control scheme is proposed based on the non-cooperative bargaining game. First, vehicles approaching intersections are divided into clusters. By introducing a simple channel-load estimation scheme, our bargaining game is presented by which the cluster leaders could negotiate an optimal combination of the transmitting power and packet generation rate for their members. When the Nash Equilibrium of our game is reached, the utility of each player will be maximized without making the channel congested. Numerical results show that our scheme could alleviate the possible packets collisions thus reducing the average experienced delay and increasing the packets delivery ratio on the receiver side.